Anatomo‐Functional Mapping of the Primate Mesencephalic Locomotor Region Using Stereotactic Lesions. Issue 5 (10th January 2020) - Gay, Marion; Belaid, Hayat; Rogers, Alister; Pérez‐García, Fernando; Roustan, Maxime; Bardinet, Eric; François, Chantal; Karachi, Carine
Abstract: Background: Dysfunction of the mesencephalic locomotor region has been implicated in gait disorders. However, the role of its 2 components, the pedunculopontine and the cuneiform nuclei, in locomotion is poorly understood in primates. Objectives: To analyze the effect of cuneiform lesions on gait and balance in 2 monkeys and to compare them with those obtained after cholinergic pedunculopontine lesions in 4 monkeys and after lesions in both the cuneiform and pedunculopontine nuclei in 1 monkey. Methods: After each stereotactic lesion, we performed a neurological examination and gait and balance assessments with kinematic measures during a locomotor task. The 3‐dimensional location of each lesion was analyzed on a common brainstem space. Results: After each cuneiform lesion, we observed a contralateral cervical dystonia including an increased tone in the proximal forelimb and an increase in knee angle, back curvature and walking speed. Conversely, cholinergic pedunculopontine lesions increased tail rigidity and back curvature and an imbalance of the muscle tone between the ipsi‐ and contralateral hindlimb with decreased knee angles. The walking speed was decreased. Moreover, pedunculopontine lesions often resulted in a longer time to waking postsurgery. Conclusions: The location of the lesions and their behavioral effects revealed a somatotopic organization of muscle tone control, with the neck and forelimb represented within the cuneiform nucleus and hindlimb and tail represented within the pedunculopontine nucleus. Cuneiform lesions increased speed, whereas pedunculopontine lesions decreased it. These findings confirm the complex and specific role of the cuneiform and pedunculopontine nuclei in locomotion and suggest the role of the pedunculopontine in sleep control. © 2020 International Parkinson and Movement Disorder Society